TIGA PEREMPUAN MEMBACA IKLAN VASELINE MAN VERSI PEMAIN SEPAK BOLA - Utami, Citra Dewi (Seni Media Rekam ISI Surakarta, 2010)
Television as a cultural phenomenon and agent frame the world through language codes. Commercial advertising plays a major role in the survival of television stations and industrial commodities. Television advertising is positioned as a text. Research in cultural studies frame this media expose about how audiences read the television advertisement. The theory of representation, identity and positioning Stuart Hall audiences are used to assess the reading audience. This study aims to (a) identify about how advertising constructs male identity, (b) identify and analyze the reading of ads by the three female audience, and (c) How is the public position on these readings. The results of this study to inform a few things, (1) ad shows his role in constructing and reconstructing the male identity, (2) the public has a variety of different opinions in reading a text the same, and (3) public autonomous positioning itself as a Dominant Hegemonic, Negotiated or Oppositional Reader.Keywords: reading, representation, male identity, advertising, public female